Self-Employment in Cameroon: Do Technical Education and Credit Availability Matter? - Sewoyehbaa, Marcel; Nyounibe, Pekiaka Zebedee; Bienvenue, Mboka Nyamsi Georges (Finance & Economics Review, 2023)
Purpose: The purpose of this study was to investigate the determinants of self-employment in the Ndop Central sub-division in the North West Region of Cameroon. Specifically, the study aimed to examine the usefulness of technical education and finance in the creation of self-employment in the sub-division. Methods: Using a survey research design, data were collected from primary sources with the help of a questionnaire. The convenience sampling technique was used to collect the needed data from a sample of 384 people from three villages of the sub-division. Binary logistics was used to analyze the data. Results: Results revealed that the coefficient of technical education was significant and negative (-2.6581). This finding signifies that graduates from the technical system of education are less likely to join self-employment as compared to graduates of general education background. Also, the availability of finance was seen to have a negative effect on the probability of being self-employed (-0.0632). It implies that individuals who have easy access to loans are less likely to be self-employed. Implication: The study is expected to guide the government to revisit the curriculum and focus of technical education in the country, as regards its contribution to the unemployment problem of the country. The study also points to the fact that those who have access to loans are not those who deserve it.